Examining the relationship between firm size and external advice on legal matters and human resources by family businesses - Benito-Hernández, Sonia; López-Cózar-Navarro, Cristina; Priede-Bergamini, Tiziana (Journal of Business Economics and Management, 2014)
In this paper the authors study the relationship between the use of external advice and the size of a Spanish family business, focusing especially on the advice on legal matters and human resources, due to the importance of these particular issues for family firms. To fulfill this objective, an in-depth review of the literature has been performed, as well as an empirical study. The results show that a family nature of business has a positive impact in the use of human resources management external advice. Nevertheless, for legal advice no relationship can be found. Finally, in line with the literature and the results of the analysis, no positive relationship has been found between family business size and the use of external advice, in comparison to the results for companies in general. The scarcity of published work about the issue and the results obtained, especially those related to the use of legal advice for family business managers, make this paper useful for researchers and businesses managers.